The Influence of Problem Based Learning Weblog on Students Motivation and Learning Outcomes on Thermochemical - Ester Muliana Marpaung; Marham Sitorus (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2024)
This research aims to determine the influence of weblog media using the problem-based learning model on student motivation and learning outcomes on thermochemical material. This research was conducted at SMAN 1 Percut Sei Tuan in the 2023/2024 academic year. Sample determination was carried out using a purposive sampling technique. The sample consisted of 2 classes, namely class XI-Matlanko 2 as an experimental class (30 students) which was taught using Weblog media and class The instruments used are test instruments to measure learning outcomes and non-test instruments to measure learning motivation. The results of this research indicate that there is an influence of using a weblog using a problem-based learning model on student learning motivation by testing the sig hypothesis. 0.00 < α (0.05) and there is also an influence of using a weblog using the problem-based learning model on student learning motivation with hypothesis testing sig. 0.00 < α (0.05). Apart from that, there is a correlation between learning motivation and student learning outcomes who are taught using weblog media using the problem-based learning model with sig. 0.00 < α (0.05) and Pearson correlation 0.953 with the high category.